P3_1 Helicarrier: Highly Feasible or Hollywood Hijinks? - Houghton, Kate; Clark, Ashley; Simms, Henry; Kuzemczak, Jacek (Physics Special Topics, 2012)
<!--[if gte mso 9]> <![endif]--> <!--[if gte mso 9]> <![endif]--> <!--[if gte mso 9]> Normal 0 false false false EN-GB X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->This paper investigates the plausibility of using a fictional helicarrier, as depicted in the 2012 Marvel Avengers film, as a potential way of flying. It was concluded that the propellers could not function at the minimum frequency required to sustain flight, found to be 374RPM or 324RPM whilst functioning with three or four propellers respectively, as modern rotors would not be able to provide adequate propeller frequency for such large blades. <!--[if gte mso 9]> Normal 0 false false false EN-GB X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->